POLA PEMBINAAN DAN PENGEMBANGAN AGAMA DI KABUPATEN KAMPAR - Agustiar Agustiar (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Construction and development of religion is one of the all important sector in system National Development Of Indonesia. made of